Habitat use and its implications to functional morphology: niche partitioning and the evolution of locomotory morphology in Lake Tanganyikan cichlids (Perciformes: Cichlidae). (10th February 2016) - Colombo, Marco; Indermaur, Adrian; Meyer, Britta S.; Salzburger, Walter
Abstract : Animal locomotory morphology, i.e. morphological features involved in locomotion, is under the influence of a diverse set of ecological and behavioral factors. In teleost fish, habitat choice and foraging strategy are major determinants of locomotory morphology. In this study, we assess the influence of habitat use and foraging strategy on important locomotory traits, namely the size of the pectoral and caudal fins and the weight of the pectoral fin muscles, as applied to one of the most astonishing cases of adaptive radiation: the species flock of cichlid fishes in East African Lake Tanganyika. We also examine the course of niche partitioning along two main habitat axes, the benthic vs. limnetic and the sandy vs. rocky substrate axis. The results are then compared with available data on the cichlid adaptive radiation of neighbouring Lake Malawi. We find that pectoral fin size and muscle weight correlate with habitat use within the water column, as well as with substrate composition and foraging strategies. Niche partitioning along the benthic–limnetic axis in Lake Tanganyikan cichlids seems to follow a similar course as in Lake Malawi, while the course of habitat use with respect to substrate composition appears to differ between the cichlid assemblages of these two lakes.